Heal The World Song Lyrics by Michael Jackson: Syntactic and Semantic Study - Heri Hidayat; Ervina C M Simatupang (Jurnal Sinestesia, 2023)
This study explores the syntactic and semantic dimensions of the iconic song lyrics, "Heal the World” by the legendary artist Michael Jackson. As a timeless anthem advocating for global unity, compassion, and social responsibility, the song's linguistic elements are analyzed to unveil the intricate interplay of syntax and semantics. The investigation encompasses a syntactic analysis to examine the grammatical structures employed, revealing Jackson's skillful use of language to convey his powerful message. Additionally, a semantic study is conducted to unravel the nuanced layers of meaning embedded within the lyrics, shedding light on the artist's intent and the emotional impact on the listener. By combining these analyses, this study aims to contribute to a deeper understanding of how language, when artfully crafted, can serve as a catalyst for societal reflection and positive change. The enduring relevance of "Heal the World" underscores the importance of linguistic analysis in unpacking the multifaceted nature of impactful song lyrics. Concurrently, a detailed semantic study is conducted to unravel the multifaceted meanings embedded within the lyrics, shedding light on the nuanced layers of expression and the artist's intent. By integrating these analyses, the research aims to provide insights into how the synergy of syntax and semantics in the song contributes to its emotional impact and enduring relevance. This dual examination not only enhances our understanding of the song's linguistic construction but also highlights the intricate relationship between form and meaning in the realm of song lyrics.